Design and Production of Portable Bar Bender - K, Mariyappan; N, Karthick; Ahamed.N, Aasik; S, Gopinath; S, Pradeep.; Kumar.S, Suresh (International Journal of Engineering and Technology, 2018)
During this generation many projects and inventions are invented to reduce the man power, time, and difficulties of the work. But still some small types of works are only based on the man power because of the cost price of invention and difficult of handling of inventions. This designed and fabricated hydraulic bar bending equipment is used for bending rods, strips, angles, and bars. During some period a type of hydraulic rod bending machines only used on large scale and industrial works. In our type we simplified the design suitably for small scale construction based rod bending works.Â Â